Diffuse Large B-Cell Lymphoma and Classical Hodgkin´S Lymphoma Converge in an Unusual Presentation as a Gastric Composite Lymphoma: Case Report - Patricia Ramos; Fernanda Díaz- Sámano; Enoe Quiñonez (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2016)
An 88-year-old male, with a history of diffuse abdominal discomfort and weight loss that presented a composite gastric lymphoma (CGL) expressing CD20, BCL-6 and a high cell proliferation index in diffuse large B-cell lymphoma and positive to CD30 and C15 in typical Reed-Stemberg cells forming a Classical Hodgkin´s lymphoma. Composite lymphoma represents <5% of the occurrence of lymphoma with a poor prognosis, which were corroborated and demonstrated with a characteristic immunophenotype.